Akad Ijarah: Multijasa Financing Mechanism In Baitul Maal Wa Tamwil (BMT) - Fita Nurotul Faizah (AL-ARBAH: Journal of Islamic Finance and Banking, 2022)
Purpose - The purpose of this research is to find out how the mechanism of multijasa financing using ijarah contract and the determination of ujrah which is related to Fatwa DSN-MUI at KSPPS BMT DAMAR Fatmawati Branch Office, Semarang City.Method - The method in this research is qualitative case study type. Data were obtained through observation, interviews and documentation. Furthermore, the collected data were analyzed descriptively.Result - The results of the study state that the practice of ijarah contracts in multijasa financing at KSPPS BMT DAMAR KC Fatmawati includes: 1.) BMT acts as a provider of funds; 2.) BMT provides funds to realize the object of member rent, such as education costs, childbirth, home renovations, renting a shop. Then, the funds are handed over to the member; 3.) members can return the funds in installments. While on the determination of ujrah/fee, the BMT is guided by the nominal amount. The amount of ujrah is clearly stated at the time of the contract execution. This means that KSPPS BMT DAMAR KC Fatmawati is also a mediator between members and renters through a number of financing submitted by members. This is not in line with the obligations of sharia financial institutions, namely providing the leased goods or services provided as stated in Fatwa DSN-MUI No.09/DSN-MUI/IV/2000.Implication - This research was conducted to provide an overview of the practice of ijarah financing and the determination of ujrah at BMT and see the relationship based on Fatwa DSN-MUI Number 44 of 2004.Originality - There have been many discussions about ijarah contracts in sharia microfinance institutions/Baitul maal wat tamwil (BMT). However, there are still few who discuss multijasa financing with ijarah contracts correlated with DSN-MUI Fatwa Number 44 of 2004.